Kinetic study of adsorption and photo-decolorization of Reactive Red 198 on TiO2 surface - Dutta, S.; Parsons, Simon A.; Bhattacharjee, C.; Jarvis, Peter; Datta, S.; Bandyopadhyay, S. (Elsevier, 2009)
Recycling and reuse of wastewater after purification will reduce the environmental pollution as well as fulfill the increasing demand of water. Adsorption-based water treatment process is very popular for dye-house wastewater treatment. The present study deals with treatment of wastewater contaminated by reactive dye. TiO2 is used as adsorbent and the spent adsorbent has been regenerated by Advanced Oxidation Process (AOP), without using any other chemicals. TiO2 adsorbs dye molecules and then those dye molecules have been oxidized via a photocatalytic reaction in presence of UV irradiation. Kinetics of dye adsorption and photocatalytic oxidation reaction has been developed in this study. Photocatalyst adsorbent (TiO2) has been reused several times after regeneration. The activity of catalyst decreases after each cycle; due to poisoning cause by intermediate by-products. Kinetic of this catalyst deactivation has been incorporated with L–H model to develop the photocatalytic reaction kinetic model.
Keywords: Adsorption; Advanced oxidation process; Catalyst regeneration; Reactive Red 198; TiO2-photocatalysis; Catalyst activity